2020
DOI: 10.3390/plants9070869
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Responses of Some Endemic Plants to High Altitudes by Intensifying Antioxidants and Secondary Metabolites Content

Abstract: Most endemic plant species have limited altitudinal ranges. At higher altitudes, they are subjected to various environmental stresses. However, these plants use unique defense mechanisms at high altitudes as a convenient survival strategy. The changes in antioxidant defense system and accumulation of different secondary metabolites (SMs) were investigated as depending on altitude in five endemic endangered species (Nepeta septemcrenata, Origanum syriacum subsp. Sinaicum, Phlomis aurea, Rosa arabica, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 108 publications
(120 reference statements)
2
45
1
Order By: Relevance
“…Herein, all isolated fungal strains had the ability to produce ammonia with a varying degree after adding Nessler’s reagent to broth media ( Table 4 ). These results are inconsistent with Ripa et al [ 9 ], who reported that, out of 16 endophytic fungal strains associated with the Triticum aestivum plant, only six strains had the ability for ammonia production.…”
Section: Resultscontrasting
confidence: 94%
See 1 more Smart Citation
“…Herein, all isolated fungal strains had the ability to produce ammonia with a varying degree after adding Nessler’s reagent to broth media ( Table 4 ). These results are inconsistent with Ripa et al [ 9 ], who reported that, out of 16 endophytic fungal strains associated with the Triticum aestivum plant, only six strains had the ability for ammonia production.…”
Section: Resultscontrasting
confidence: 94%
“…Fungal endophytes are those colonized intra- or intercellular spaces of plant tissues that do not show any illness symptoms [ 6 ]. Fungal endophytes have various mechanisms to promote plant growth, including phytostimulation, biocontrol, and biofertilizations [ 7 , 8 ]; for example, plant growth-promoting fungi (PGPF) directly promote plant growth by the production of phytohormones such as indole-3-acetic acid (IAA) and gibberellic acid [ 9 ]. Fungal IAA synergistically reacts with endogenous plant IAA, which then stimulate plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…This response could help in scavenging ROS and inducing the ascorbate-glutathione cycle [8,76]. Phenolic compounds could also be involved in plant tolerance to drought stress and play a significant role as a sink for carbon under stress conditions [77,78]. These effects could explain the improvement in total soluble phenols by reducing the irrigation level in this study ( Figure 4C).…”
Section: Discussionmentioning
confidence: 75%
“…The accumulation of secondary metabolites is reported to have a vital role in tolerance to environmental biotic and abiotic stresses. These secondary metabolite help in the adaptation of stressed plants to different environmental conditions, for example, the accumulation of phenols and flavonoids as antioxidants [ 19 ].…”
Section: Discussionmentioning
confidence: 99%